2014
DOI: 10.1016/j.bpj.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reconstitution of a CaMKII Memory Switch by an NMDA Receptor-Derived Peptide

Abstract: Ca(2+)/Calmodulin-dependent protein kinase II (CaMKII) has been shown to play a major role in establishing memories through complex molecular interactions including phosphorylation of multiple synaptic targets. However, it is still controversial whether CaMKII itself serves as a molecular memory because of a lack of direct evidence. Here, we show that a single holoenzyme of CaMKII per se serves as an erasable molecular memory switch. We reconstituted Ca(2+)/Calmodulin-dependent CaMKII autophosphorylation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…5, information is stored because a dynamic process maintains the level of phosphorylated CaMKII. The plausibility of this dynamic process was tested in reconstitution experiments using purified proteins (Urakubo et al, 2014). It was shown that a simple chemical system containing CaMKII, calmodulin, protein-phosphatase 1, and a peptide fragment containing the CaMKII-binding site on the NMDA channel could function as a switch.…”
Section: Discussionmentioning
confidence: 99%
“…5, information is stored because a dynamic process maintains the level of phosphorylated CaMKII. The plausibility of this dynamic process was tested in reconstitution experiments using purified proteins (Urakubo et al, 2014). It was shown that a simple chemical system containing CaMKII, calmodulin, protein-phosphatase 1, and a peptide fragment containing the CaMKII-binding site on the NMDA channel could function as a switch.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reconstitution experiments directly demonstrate this mechanism (Urakubo et al, 2014). These experiments utilized purified CaMKII, protein phosphatase 1 (PP1), and a peptide fragment of NR2B.…”
Section: Principle 1: Intersubunit Autophosphorylation Of T286 Maintamentioning
confidence: 95%
“…An important finding of the reconstitution experiments of (Urakubo et al, 2014) is that the switch was not stable in the absence of NR2B (see also (Bradshaw et al, 2003)). From a theoretical standpoint, this is not unexpected, given that the experiments were conducted under conductions of CaMKII holoneyzme concentration (2.7 micromolar) much less than the concentration in the PSD (~50 micromolar); thus, the saturation of PP1 that promotes the stability of the on state was below what would be expected in the PSD (Zhabotinsky, 2000).…”
Section: Principle 2: In the On State Dephosphorylation Of T286 Becomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CaMKII possesses bi-stability in their model, in which the model’s intracellular signaling was adopted from a previous model with CaMKII bi-stability24. It should be noted here that CaMKII has sometimes been hypothesized to function as a bi-stable memory element at postsynaptic spines during the induction of long-term potentiation245960101, while such bi-stable character has not been observed by an in vivo imaging of CaMKII activity in dendritic spines102. Related to this controversy, our reverse-engineered model suggested monotonical dose-response of CaMKII, instead of more complicated one like with hysteresis; the former never produces bi-stability.…”
Section: Discussionmentioning
confidence: 99%